Does chemical preconditioning contribute to the effectiveness of scaling and root planing? An in vitro pilot investigation. Issue 1 (28th November 2016) - Becker, M; Ciupka, J; Pierchalla, T; Fischer, KR; Friedmann, A
Abstract: Objectives: A solution based on hypochlorite and amino acids was introduced to improve cleaning efficacy on the root surfaces. The purpose of this in vitro pilot study was to evaluate the time reduction and number of strokes required to clean untreated root surfaces in vitro . Methods: Sixty extracted human teeth displaying areas with subgingival calculus were assigned equally to one of three treatment groups ( n = 20) according to the size of occupied areas, estimated by the number of pixels. The groups were assigned to either 30 s penetration time (I) or 300 s (II) or no pretreatment application (III). The weight for instrumentation was calibrated for a M25A curette (Deppeler/Switzerland) with 500 g. A new set of tools was used for each group, and each instrument was sharpened after single use by an EasySharp Device (Deppeler/Switzerland). Results: The time (in seconds) for instrumentation was recorded as follows: Group I: 32/23.5/50 (median/first quartile/third quartile); group II: 33/20/52.5; group III: 46.5/35.5/52.3. The results for the numbers of strokes were: Group I: 18/14.3/28; group II: 18.5/13/30.5; group III: 17.5/15/25. No statistically significant differences ( P < 0.05) were found between the three groups for the variables 'time' and 'number of strokes'. Conclusions: Within the limits of this in vitro pilot study, preconditioning of the calculus on root surfaces with an alkaline solution failed to reduce the number of strokes and time of instrumentation significantly.